Small molecule inhibitors targeting tec kinase block unconventional secretion of fibroblast growth factor 2 - La Venuta, Giuseppe; Wegehingel, Sabine; Sehr, Peter; Müller, Hans-Michael; Dimou, Eleni; Steringer, Julia P.; Grotwinkel, Mareike; Hentze, Nikolai; Mayer, Matthias P.; Will, David W.; Uhrig, Ulrike; Lewis, Joe D.; et al. (The journal of biological chemistry, 2016)
Fibroblast growth factor 2 (FGF2) is a potent mitogen promoting both tumor cell survival and tumor-induced angiogenesis. It is secreted by an unconventional secretory mechanism that is based upon direct translocation across the plasma membrane. Key steps of this process are (i) phosphoinositide-dependent membrane recruitment, (ii) FGF2 oligomerization and membrane pore formation, and (iii) extracellular trapping mediated by membrane-proximal heparan sulfate proteoglycans. Efficient secretion of FGF2 is supported by Tec kinase that stimulates membrane pore formation based upon tyrosine phosphorylation of FGF2. Here, we report the biochemical characterization of the direct interaction between FGF2 and Tec kinase as well as the identification of small molecules that inhibit (i) the interaction of FGF2 with Tec, (ii) tyrosine phosphorylation of FGF2 mediated by Tec in vitro and in a cellular context, and (iii) unconventional secretion of FGF2 from cells. We further demonstrate the specificity of these inhibitors for FGF2 because tyrosine phosphorylation of a different substrate of Tec is unaffected in their presence. Building on previous evidence using RNA interference, the identified compounds corroborate the role of Tec kinase in unconventional secretion of FGF2. In addition, they are valuable lead compounds with great potential for drug development aiming at the inhibition of FGF2-dependent tumor growth and metastasis.